Probing Nitrogen‐Doping Effects in the Core‐Shell Structured Catalysts for Bifunctional Electrocatalysis. Issue 19 (6th August 2018) - Li, Qianru; Wan, Gang; Zhao, Wanpeng; Yang, Ce; Peng, Chunlei; Duan, Zhengli; Chen, Hangrong
Abstract: The design of core‐shell structured catalysts has attracted wide interests due to their remarkable catalytic performances in many fields. Although the nitrogen doping is often integrated in such kind of catalysts, the main contribution is exclusively attributed to the metal sites or the core‐shell configuration. The role of nitrogen doping is often believed to be less important, which remains largely unexplored. Here, in an effort to probe the catalytic role of heterogeneous doping in such core‐shell structure, the effect of nitrogen doping on the activation of cobalt and iron carbide‐based materials for the electrocatalytic reduction of oxygen and the hydrogen evolution reaction is originally revealed. The nitrogen doping in the core‐shell structured biphasic interfaces is found to be of critical importance for triggering the electrocatalytic activity and selectivity. Therefore, this study shows the neglected but critical role of nitrogen doping and biphasic interactions in a core‐shell configuration, paving a new pathway towards the performance enhancement. Abstract : When small is big : Trace‐nitrogen‐doping induced activation of core‐shell structured biphasic interfaces for ORR activity and selectivity, as well as HER activity in acidic media is originally demonstrated, highlighting the neglected while critical role of the synergistic electrocatalysis between the nitrogen doping and the biphasic interactions in the iron carbide or cobalt nanoparticles‐based core‐shell structured catalysts.